2019
DOI: 10.7770/safer-v0n0-art1658
|View full text |Cite
|
Sign up to set email alerts
|

Carcass, Organ Weights and Egg Quality Characteristics of Guinea Fowl Layers Fed Varying Levels of Butter Fly Pea Leaf (Centrosema Pubescent) Meal.

Abstract: This study was conducted to investigate the effects of different protein levels on growth of guinea fowl keets (Numidia meagris) of the same age under intensive system in a typical poultry house from 6th week to 12th week of age. They were fed commercial broiler starter for two weeks and maintained on same diet of 18% crude protein for 5 weeks of age and given water ad libitum. The birds were separated into three pens. One hundred and twenty old guinea fowls were assigned at grower period on 3 dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Similarly, the dressing percentage (DP) for poultry meat from the current study ranged from 72.2 to 74.8%, which is in agreement with the average DP value of 73% (Muth et al, 2006). Moreover, the 75.4% DP of the GF reared under intensive management system (Ahaotu et al, 2019) and 72.8% for PK at 15 weeks of age (Melesse et al, 2013) were in line with the current findings.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, the dressing percentage (DP) for poultry meat from the current study ranged from 72.2 to 74.8%, which is in agreement with the average DP value of 73% (Muth et al, 2006). Moreover, the 75.4% DP of the GF reared under intensive management system (Ahaotu et al, 2019) and 72.8% for PK at 15 weeks of age (Melesse et al, 2013) were in line with the current findings.…”
Section: Discussionsupporting
confidence: 89%
“…The shell percentage of guinea fowl eggs was 15.23, and 15.60 % was found by (Vekić et al, 2018;Mohsenpour et al, 2020). Lower findings are 12.84 % reported by (Ahaotu et al, 2019), but there are also higher values, such as 18.3% (Zelleke et al, 2020).…”
Section: Rayan Gn Mansour a Fathi MMmentioning
confidence: 66%
“…Musundire et al (2017) reported that Guinea fowls outweighed chickens in terms of having higher body weight, carcass weight, cold dressed weight, and breast weight except for dressing percentage for both species (chickens and helmeted guinea fowls); proportions were comparable. A study by Ahaotu et al (2019) in Nigeria and a survey by Zelleke et al (2022) in Ethiopia reported a higher dressing percentage (75.4 and 73.8 %, respectively) for guinea fowl in comparison with a survey by Musundire et al (2017) in Zimbabwe that found that average was (64.1 %) only. The same trend observed for the breast percentage trait.…”
Section: Carcass Yield and Meat Qualitymentioning
confidence: 70%
See 2 more Smart Citations